Analysis of Smile Characteristics in Dental students of Lahore Medical and Dental College, Lahore - Sajid Naeem, Warda Amjad, Maham Nayyar, Hira Javaid Sukhera, Muhammad Abubakar, Ahmad Naveed Virk, Khezran Qamar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate different smile characteristics among dental students and find out gender- based association. Study design: Cross sectional observational study. Place and duration: Prosthodontic Department of Lahore Medical And Dental College, Lahore, from 1st Jan 2022, till 1st April 2022. Methodology: A total of 260 dental students were assessed for smile characteristics i.e.; smile line, smile arc, labiodental relationship and number of teeth visible during posed smile. Result: The smile line frequently observed was average smile line 52.7% followed by gummy smile line 22.3%. More male participants had average smile line whereas gummy smile line was frequently found in females. Frequently observed smile arc was consonant 63.1% followed by flat arc 22.3% and least observed arc was reverse 14.6%. Most of the participants display second premolar to second premolar teeth during posed smile 41.9%. Female display teeth up to first molar 51.5% and males up to second premolars 48.7%. Labiodental relationship frequently observed was the relation of the lips not touching the incisors 54.2%. Gender based difference with respect to smile line, smile arc, and number of displayed teeth was significant p<0.05, however labiodental relationship was insignificantly found among gender p> 0.05. Conclusion: Restorations in esthetic zone should be carried out considering smile characteristics like smile arc, smile line, labiodental relation and teeth display. Gender dimorphism should be considered as an important factor that can influence the esthetic outcome of restorations. Keywords: Gum display, Labiodental relation Smile line, smile arc, smile design, tooth display,